Pengembangan E-learning untuk Meningkatkan Pemecahan Masalah Matematika - RA Seravika Primasari (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
This literature discusses the development of customized E-learning for mathematics education, with a specific focus on enhancing problem-solving skills. The study examines various types of E-learning tools, including websites, e-modules, and Android applications. By integrating innovative technology into mathematics education, this review emphasizes the crucial role of E-learning in facilitating interactive learning experiences and improving students' problem-solving abilities. The expected outcomes of this research include the creation of effective and engaging E-learning modules, improvement of students' mathematical abilities, and the development of a deep understanding of problem-solving strategies. Through a comprehensive analysis of various E-learning approaches, this literature review aims to provide valuable insights into the advanced education world, creating a more empowering learning environment for mathematics students.